Multinational Enterprises, Foreign Direct Investment and Growth in Africa South African Perspectives - Gilroy, Bernard Michael; Gries, Thomas; Naudé, Willem A. (Contributions to Economics,, 2005)
How can Africa, the world's most lagging region, benefit from globalisation and achieve sustained economic growth? Africa needs greater investment by Multinational Enterprises (MNEs) to improve competitiveness and generate more growth through positive spill-over effects. Despite the fact that Africa's returns on investment averaged 29% since 1990, Africa has gained merely 1% of global Foreign Direct Investment (FDI) flows. The challenge for African countries is how to be a more desirable destination for FDI. The study integrates three currents of economic research, namely from the literature on (endogenous) economic growth, convergence and regional integration, the explanations for Africa's poor growth and the growing understanding of the role of MNEs in a global economy. The empirical side of the book is based on an econometric study of the determinants of FDI in Africa as well as a detailed firm-level survey conducted in 2000.